Development and Evaluation of Learning Module for Special Program in Journalism - Richard Brian Tutor (ASEAN Multidisciplinary Research Journal, 2021)
The study aimed to develop and evaluate a learning module for Special Program in Journalism (SPJ) for junior high school using a descriptive method. The developed learning module was evaluated by 10 experts from the Division of Rizal and 20 student publication advisers from selected public high schools. The evaluation was determined by a five-point Likert scale focusing on the six aspects; authenticity, clarity; comprehensibility, creativity, technical quality, and usability. The statistical tools used were weighted mean and individual sample t-test. The results of the study revealed that the experts and student publication adviser-respondents evaluated the developed learning module as Very Highly Agree in all aspects as evidenced by the overall weighted mean ratings of 4.89 and 4.90, respectively.